2022
DOI: 10.1111/anae.15700
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular subphenotypes in patients with COVID‐19 pneumonitis whose lungs are mechanically ventilated: a single‐centre retrospective observational study

Abstract: Summary Unsupervised clustering methods of transthoracic echocardiography variables have not been used to characterise circulatory failure mechanisms in patients with COVID‐19 pneumonitis. We conducted a retrospective, single‐centre cohort study in ICU patients with COVID‐19 pneumonitis whose lungs were mechanically ventilated and who underwent transthoracic echocardiography between March 2020 and May 2021. We performed latent class analysis of echocardiographic and haemodynamic variables. We characterised the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…showed that right ventricular dilatation, analogous to early injury, was associated with renal dysfunction and increased mortality [ 5 ]. Over half of those with the ‘class 2’ phenotype (isolated dilatation) required renal replacement therapy [ 1 ]. This could plausibly be associated with multisystem thrombotic disease, for which higher doses of low molecular weight heparin are now titrated with plasma anti‐Xa monitoring.…”
Section: Defining Acute Right Ventricular Injurymentioning
confidence: 99%
See 4 more Smart Citations
“…showed that right ventricular dilatation, analogous to early injury, was associated with renal dysfunction and increased mortality [ 5 ]. Over half of those with the ‘class 2’ phenotype (isolated dilatation) required renal replacement therapy [ 1 ]. This could plausibly be associated with multisystem thrombotic disease, for which higher doses of low molecular weight heparin are now titrated with plasma anti‐Xa monitoring.…”
Section: Defining Acute Right Ventricular Injurymentioning
confidence: 99%
“…Chotalia et al. labelled the class 3 phenotype as ‘right ventricular failure’ [ 1 ]. In this class: 23% required a second vaso‐active agent; 31% had normal left ventricular ejection fraction; and 56% had a hyperdynamic left ventricle.…”
Section: Defining Acute Right Ventricular Injurymentioning
confidence: 99%
See 3 more Smart Citations